2021
DOI: 10.3390/w13213091
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Evaluation of the Possible Occurrence of Pesticides in Groundwater Contaminated with Nitrates—A Case Study from Southern Poland

Abstract: This paper addresses groundwater pollution and the potential presence of pesticides within the catchment areas of two reservoirs that are sources of drinking water. The two reservoirs are Goczałkowice and Kozłowa Góra, both in Southern Poland. Agricultural and rural areas dominate both catchments. Archival data showed local groundwater contamination with nitrates. This indicated the possible presence of pesticides in shallow groundwater. In total, 13 groundwater samples from shallow sandy aquifers were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Among the groundwater samples, the highest concentrations of NO 3 − were reported for W2, which exceeded the drinking water limit (i.e., 50 mg/L [38]) in two sampling campaigns. In the past, elevated concentrations of NO 3 − in groundwater from this well were also observed [39]. Given the land use in the vicinity of these wells, the probable source of nitrate is agricultural activities, i.e., the application of manure or fertilisers.…”
Section: Discussionmentioning
confidence: 88%
“…Among the groundwater samples, the highest concentrations of NO 3 − were reported for W2, which exceeded the drinking water limit (i.e., 50 mg/L [38]) in two sampling campaigns. In the past, elevated concentrations of NO 3 − in groundwater from this well were also observed [39]. Given the land use in the vicinity of these wells, the probable source of nitrate is agricultural activities, i.e., the application of manure or fertilisers.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study, groundwater polluted with pesticides was found to increase susceptibility to estrogen-mediated cancers, in spite of the ban on these chemicals for decades [ 46 ]. Likewise, alarmingly high levels of these chemicals have also been reported from other regions of the world in recent studies [ 47 , 48 , 49 ]. Additionally, a Brazilian study from the year 2022 linked pesticide residue with an increased risk of cancer in one province [ 50 ].…”
Section: Evidence Of Xeno-estrogenicitymentioning
confidence: 81%
“…Ślósarczyk et al [9] presented the potential presence of pesticides within the catchment areas of Goczałkowice and Kozłowa Góra reservoirs (Southern Poland) that are destined for drinking water supply. Agricultural and rural areas dominate both catchments.…”
Section: Groundwater Vulnerability To Pollution Assessment Filomena C...mentioning
confidence: 99%